The feasibility and acceptability of smart home technology using the Howz system for people with stroke. (17th February 2020) - Rogerson, Louise; Burr, Jonathan; Tyson, Sarah
Abstract: Purpose: To assess the feasibility and acceptability of the Howz smart home system for stroke survivors. Materials: Howz uses smart home technology to monitor users' activity in the home and machine learning algorithms to detect when their activity changes. This information made available to the user and a named contact (usually a family member) via the Howz app. If activity changes, an alert is then sent to the user and the named contact. Methods: Howz was installed in the homes of 19 stroke survivors who lived alone. The sensors installed; the number and nature of alerts; adverse events; any technical difficulties and how Howz was used were recorded. We also interviewed participants and their named contacts about their views and experiences of using Howz eight weeks after installation. Results: Installation was effective; no technological problems or adverse events were reported. All participants chose alerts regarding "getting up" and activity during the day and at night. There was a mean of 1.1 (sd 1.2) alerts/person. Participants found the system unobtrusive and were positive about it. They found it easy to use and would recommend it to others with stroke. The most frequently reported benefit was that Howz gave peace of mind for the users and/or the family/named contact that help would be at hand if needed. Conclusions: The Howz system was feasible and acceptable for stroke survivors. It gave users and their family an enhanced sense of security and peace of mind that help would be at hand if needed. Implications for rehabilitation: Although most stroke survivors are elderly and often suffer physical, visual and cognitive disabilities which are often considered as barriers to using smart home technology, this project has demonstrated the well-developed smart home technology is feasible and acceptable. Users were able and willing to engage with the technology (to varying degrees) and had no concerns about invasion of privacy. The main benefit of the Howz system is an enhanced sense of security for the user and their family that help is at hand if needed.